2011
DOI: 10.1007/s11604-010-0551-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computed tomographic measurement of a cross-sectional area of a small pulmonary vessel in nonsmokers without airflow limitation

Abstract: There was a significant correlation between pulmonary small vascular alteration and airflow impairment even in nonsmokers without airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…We also found a significant association between the CSA of small pulmonary vessels and other clinical variables. For instance, FEV 1 /FVC was the independent determinant predicting the CSA of small pulmonary vessel in non‐smokers and smokers and a previous study obtained similar results in non‐smokers without significant airflow obstruction . Based on pathological specimens, it was reported that pulmonary vascular remodeling occurs because of smooth muscle cell proliferation and elastin and collagen deposition in smokers without airflow obstruction .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We also found a significant association between the CSA of small pulmonary vessels and other clinical variables. For instance, FEV 1 /FVC was the independent determinant predicting the CSA of small pulmonary vessel in non‐smokers and smokers and a previous study obtained similar results in non‐smokers without significant airflow obstruction . Based on pathological specimens, it was reported that pulmonary vascular remodeling occurs because of smooth muscle cell proliferation and elastin and collagen deposition in smokers without airflow obstruction .…”
Section: Discussionmentioning
confidence: 55%
“…For instance, FEV 1 /FVC was the independent determinant predicting the CSA of small pulmonary vessel in non-smokers and smokers and a previous study obtained similar results in non-smokers without significant airflow obstruction. 25 Based on pathological F I G U R E 2 Correlations between the amount of smoking, small pulmonary vascular alteration and arterial stiffness in smokers. A, The packyears was significantly correlated with %CSA<5 (r = −0.631, P < 0.001) in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on pulmonary vessels. Recently, Matsuoka et al proposed the cross-sectional area (CSA) of small pulmonary vessels as a parameter of pulmonary vessel alterations in patients with COPD [10][11][12]. They reported that in case of severe emphysema the total CSA of sub-subsegmental vessels correlated with the mean pulmonary arterial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, 27 an orientation vector field o is generated to refine the tree structure by solving the global optimization problem delineated in Eq. (6). This equation makes the orientation vectors similar to the edge direction and maintains a similar direction between a vertex v i and its…”
Section: Ivb Refinementmentioning
confidence: 99%
“…Recently, several studies suggested that vascular alteration is closely related to endothelial dysfunction 2 which is claimed to be related to emphysema. 3,4 From this point of view, Matsuoka and co-workers 5,6 recently attempted to show a correlation between the area of small pulmonary vessels and pulmonary function tests (PFT). To find small vessels, they select circular regions whose areas were less than 5 mm 2 after simple thresholding in a 2D computed tomography (CT) slice.…”
Section: Introductionmentioning
confidence: 99%